Bioactive Constituents from Radermachera boniana. Issue 8 (6th June 2016) - Wang , Ming‐Zhong; Xie, Wen‐Jian; Guan , Yi‐Fu; Song , Xun; Hung, Nguyen Van; Cuong, Nguyen Manh; Santarsiero, Bernard D.; Fong, Harry H.S.; Soejarto, D. Doel; Zhang , Hong‐Jie
Abstract: The bioassay‐directed fractionation of the roots of Radermachera boniana Dop. (Bignoniaceae) led to the isolation of 17 naphthalene‐based quinones and related derivatives including the new radermacherones A (1 ), B (2 ) and C (6 ), radermaquinone (3 ), and radermacherol (5 ). The absolute configuration of2 was determined through X‐ray crystallographic analysis. The isolates3, hydroxy‐β‐isonaphthoquinone (4 ), 6, α‐naphthoquinone (8 ), β‐naphthoquinone (9 ), 3‐hydroxy‐β‐naphthoquinone (10 ), 4‐oxo‐β‐naphthoquinone (11 ), 2‐acetyl‐naphtha[2, 3‐b]furan‐4, 9‐dione (BBI608) (12 ), 2‐acetyl‐7‐methoxy‐naphtho[2, 3‐b]furan‐4, 9‐dione(13 ), stenocarpoquin‐one B (14 ), dehydro‐α‐isonaphthoquinone (15 ) and 3‐hydroxydehydro‐α‐isonaphthoquinone (16 ) showed cytotoxic activity in a cancer cell line panel comprising KB, Col‐2, Lu‐1 and MCF‐7 with IC50 values ranging from 0.15‐38.6 µM. Compounds12 (known as BBI608) and its methoxy derivative, 13 with extended conjugation showed the highest cytotoxicity among the tested compounds with IC50 values ranging from 0.12‐3.33 µM, but13 showed much different cancer cell killing selectivity than12 . Abstract : The bioassay directed‐fractionation of the roots of Radermachera boniana led to the isolation of 17 naphthalene‐based quinones and related derivatives including five new ones. Several of them demonstrated potent inhibition and selective activity against cancer cells.